University students’ purchase preferences towards foreign and domestic branded apparel / Hiew Shu Yin and Susan Chin Tee Suan - Hiew, Shu Yin; Chin, Susan Tee Suan (2012)
The purpose of this study is to examine the purchase preferences towards foreign and domestic branded apparels. A total of 200 students took part in this survey. It was found that preferences towards foreign branded apparels are related to the level of purchasing power and is not related to the demographics variables. 58% of the students surveyed preferred foreign branded apparel. There is a positive relationship between media influence and preferences towards foreign/domestic branded apparels. The more a person is exposed to the media, the stronger will be the influence of the media in “persuading” the individual to purchase the apparel.